The Great White Way : race and the Broadway musical - Hoffman, Warren, 1976- (Rutgers University Press, 2020)
"The initial publication of The Great White Way was and remains the first and only book-length investigation into the ways in which race and ethnicity have shaped the American musical over the course of the twentieth century up through today. In addition to the musicals mentioned above, the book contains analyses of Tony Award-winning shows A Chorus Line, 42nd Street, and The Will Rogers Follies, as well as an examination of the role of casting practices in the musical, particularly the phenomenon of African American and interracial productions of Broadway musicals. Now updated to include a discussion of the blockbuster musicals Hamilton and The Book of Mormon, as well as other developments of the musical in recent years, The Great White Way provides both lovers of the musical and academics with a probing looking at the ways in which issues of race and ethnicity shape this all-American art form." This second edition will reflect new developments that have occurred in the world of the Broadway musical in recent years. Chapter four will be revised and an entire new chapter will be added about smash hits The Book of Mormon and Hamilton, which are both incredibly important when analyzing race and the Broadway musical. Hoffman will also include a new Afterword that will bring the book up to the 21st century and elaborate on what is happening off-Broadway as well"--